2018
DOI: 10.1111/psyp.13221
|View full text |Cite
|
Sign up to set email alerts
|

The effects of breathing at a frequency of 0.1 Hz on affective state, the cardiovascular system, and adequacy of ventilation

Abstract: The present study aimed to investigate changes induced by breathing at 0.1 Hz in affective state, cardiovascular activity, and adequacy of ventilation as well as the relation between changes in peripheral physiological processes and alteration of affect. Eighty-three participants were randomly assigned to one of three groups: Two groups doing paced breathing at 0.1 Hz, one with and the other without a cover story hiding the goal of the experiment, and, as a control, paced breathing at 0.28 Hz. We measured the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 102 publications
6
25
0
Order By: Relevance
“…Thus, the present study suggests that training increases the relaxing effects of paced breathing at 0.1 Hz and makes it more pleasurable. Therefore, the lack of effects of paced breathing on affect reported by some previous studies could be caused by the participants’ lack of experience with paced breathing [44, 45, 46, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the present study suggests that training increases the relaxing effects of paced breathing at 0.1 Hz and makes it more pleasurable. Therefore, the lack of effects of paced breathing on affect reported by some previous studies could be caused by the participants’ lack of experience with paced breathing [44, 45, 46, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, paced breathing prevents the use of compensatory mechanisms such as apnea. As a result, some untrained participants tend to hyperventilate during slow paced breathing [26, 27, 28]. Hyperventilation leads to a decrease in arterial pressure of CO 2 , and when this decrease is large enough it causes several undesirable physiological and psychological changes, such as increase in heart rate, paresthesia and tetany, dizziness, lightheadedness, and increased emotional arousal [29, 30, 31, 32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, one participant experienced dizziness during the resting period prior to the main test; therefore, this is not likely to be due to the intervention. One concern during controlled/deep breathing exercises is hyperventilation (Szulczewski & Rynkiewicz, ). In our study, the load of 5 cmH 2 O, but not 10 cmH 2 O, was associated with lower EtCO 2 compared to the no load condition.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely studied and used paced breathing is at frequencies around 0.1 Hz (six breaths per minute) because this frequency maximizes the amplitude of cardiovascular-oscillations (Pitzalis et al 1998; Song and Lehrer 2003). Breathing at 0.1 Hz has been used as an emotion regulation tool (Laborde et al 2016; Zautra et al 2010), as an experimental procedure in basic research on breathing (Chalaye et al 2009; Szulczewski and Rynkiewicz 2018), as a method of measurement of vagal tone (Grossman et al 1990; Shields 2009), and as a behavioral treatment for hypertension (Zou et al 2017). Breathing at frequencies around 0.1 Hz is also used in biofeedback-based methods aimed at increasing heart rate variability (Lehrer et al 2000), which has shown promising effects in the treatment of, for example, anxiety (Goessl et al 2017), depression (Hassett et al 2007; Siepmann et al 2008), and fibromyalgia (Hassett 2007).…”
mentioning
confidence: 99%